1982
DOI: 10.1139/y82-085
|View full text |Cite
|
Sign up to set email alerts
|

Cross-adaptive responses to different forms of leg training: skeletal muscle biochemistry and histochemistry

Abstract: The influence of a program of high intensity training and of a combined program of high intensity training and prolonged submaximal training on adaptations to the vastus lateralis muscle was investigated in two groups of elite athletes. The high intensity training (H) consisted of ice hockey practices and games over a 14-week period while the combined program (HI-LO) included the addition of supplementary sessions of cycling, three times per week, progressively increasing from 30 to 45 min per session and at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
3
1

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 4 publications
1
12
3
1
Order By: Relevance
“…The present data showing a similar increase in capillarization around type I and type II fibre types therefore suggest that recruitment of a greater fraction of type II fibres than is recruited with exercise of moderate intensity does not lead to growth of capillaries specifically around type II fibres. This is somewhat in contrast to an earlier study by Daub et al (1998) involving high intensity training, in which an increase in capillaries per fibre area was found for type I fibres, and not for type II fibres (Daub et al 1982). It should be pointed out, however, that in this latter study by Daub et al (1982) the training did not increase C: F ratio; in fact, a decrease in C: F ratio was observed for type II fibres.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present data showing a similar increase in capillarization around type I and type II fibre types therefore suggest that recruitment of a greater fraction of type II fibres than is recruited with exercise of moderate intensity does not lead to growth of capillaries specifically around type II fibres. This is somewhat in contrast to an earlier study by Daub et al (1998) involving high intensity training, in which an increase in capillaries per fibre area was found for type I fibres, and not for type II fibres (Daub et al 1982). It should be pointed out, however, that in this latter study by Daub et al (1982) the training did not increase C: F ratio; in fact, a decrease in C: F ratio was observed for type II fibres.…”
Section: Discussioncontrasting
confidence: 99%
“…This is somewhat in contrast to an earlier study by Daub et al (1998) involving high intensity training, in which an increase in capillaries per fibre area was found for type I fibres, and not for type II fibres (Daub et al 1982). It should be pointed out, however, that in this latter study by Daub et al (1982) the training did not increase C: F ratio; in fact, a decrease in C: F ratio was observed for type II fibres. No single variable used to express capillarization will give a complete description of capillary supply.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, information about the effect of a period of interval training on muscle capillarization in trained runners is sparse. In agreement with present findings, we and others have previously shown that high‐intensity interval running is less effective in improving capillarization than prolonged running (Daub et al., ; Nybo et al., ; Kohn et al., ). The reason why the 10‐20‐30 training did not induce capillary growth could be that that 10‐20‐30 training evokes a weak angiogenic stimuli compared with moderate‐intensity exercise training.…”
Section: Discussionsupporting
confidence: 94%
“…During a typical practice, a short warm-up period will occur along with repeat bouts of high-intensity skating, instruction, special plays and controlled scrimmages, all within 1.5-2 h (Daub et al 1982). Two to three games can be played in a week during the season, with practices usually held on non-game days.…”
Section: Training Practicesmentioning
confidence: 99%